(untitled) - Bozeman, Adda B. (New Yersy, 1960)
This book has been informed by these reflections. However, it does not pretend to incorporate the whole mythology and reality of all of the world's cultures and nation. It is neither a consecutive exposition of what has often been termed world history, nor a systematic study of the whole context of international and intercultural,...
Keywords: International relations; History